An updated review of recent advances on modified technologies in transcritical CO2 refrigeration cycle. (15th December 2019) - Yu, Binbin; Yang, Jingye; Wang, Dandong; Shi, Junye; Chen, Jiangping
Abstract: With carbon emission levels on the rise, rapid and far-reaching action is needed to counteract global warming. Among many available strategies, CO2 is nowadays more and more often proposed as a solution for heating, cooling and refrigeration purposes since the extremely low global warming potential and being natural. In order to overcome the inherently low efficiency in high-temperature conditions and high operating pressure especially in transcritical cycles, an updated review of the advances on modified technologies to solve the drawbacks of CO2 refrigeration is provided and recent progress on the energy efficiency improvement is summarized. First, the basic principles of the CO2 refrigeration cycle and important performance characteristics are discussed. Then, a detailed discussion on different modified technologies as well as their operating fundamental, technical features and performance are provided, followed by a summary of previous studies. At the end of this review, conclusion and perspectives on the future development of this field are presented. Highlights: The principles of the CO2 refrigeration cycle and performance are discussed. A detailed discussion on different modified technologies is provided. Recent progress on the energy efficiency improvement is summarized. Perspectives on the future development, research opportunities are presented.